Upholding "good science" in human origins research: A response to Chan et al (2019) - Ackermann, Rebecca, Rogers; Athreya, Sheela; Black, Wendy; Cabana, Graciela; Hare, Vincent; Pickering, Robyn; Schroeder, Lauren (My University, 2019)
The recent publication by Chan et al (2019) entitled “Human origins in a southern African palaeo-wetland and first migrations” fails to meet scientific standards for publication in two ways. First, it neglects its scientific duty to discuss the entire body of scientific evidence around human origins, which leads to unsupportable claims. Second, it reinforces racialized power dynamics within the science of human origins. We argue that the authors would have benefitted from a more diverse team that included social scientists and humanists, and that the editorial process failed to uphold thorough and morally responsible science.
Keywords: Colonial practice; human evolution; human origins; Khoesan diversity; race and racism